(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article examines the state of pharmacological research in Uzbekistan, focusing on the development and production of specialty drugs and their role in export sales. The study analyzes the progress achieved in the pharmaceutical sector, key export markets, and strategies employed to enhance the global competitiveness of Uzbek drugs. Challenges and opportunities within the industry are also explored, offering insights into future growth trajectories.